The Administrative Judge’s Approaches to Competitive Economic Dispute - Bouarroudj, Chouaib (Journal of Human Sciences, 2025)
Administrative justice has undergone a recent evolution due to the political, social and economic development that the world is experiencing, which has led to the opening up of the administrative judge to the competitive economic field. At a time when competitive disputes between economic operators on the market are multiplying. As the Algerian legislator has entrusted the Competition Council with the task of ensuring that competition functions properly, this study aims to show how the administrative judge deals with modern economic disputes linked to competition litigation, in order to achieve administrative justice and thus contribute to the establishment of the state of law.